LEGAL RESPONSIBILITY FOR DECISIONS MADE BY ARTIFICIAL INTELLIGENCE - Mardonova Aziza Jamolovna (Modern American Journals, 2025)
The rapid advancement of Artificial Intelligence (AI) has revolutionized decision-making across sectors such as healthcare, finance, and public administration. However, as AI systems become increasingly autonomous, determining legal responsibility for their actions has emerged as a major global challenge. This article analyzes the legal liability frameworks surrounding AI decisions, focusing on the European Union’s AI Liability Directive, Uzbekistan’s national AI initiatives, and comparative approaches in the United States, Japan, and China.
Keywords: Artificial Intelligence, legal responsibility, Directive, civil law, international cooperation, national strategies.